Magnetotelluric studies across the Damara Orogen and Southern Congo craton - Khoza, Tshepo David (My University, 2016)
Archean cratons, and the Proterozoic orogenic belts on their flanks, form an integral part of the Southern Africa tectonic landscape. Of these, virtually nothing is known of the position and thickness of the southern boundary of the composite Congo craton and the Neoproterozoic Pan African orogenic belt due to thick sedimentary cover. In this work I present the first lithospheric-scale geophysical study of that cryptic boundary and define its geometry at depth. The results are derived from two-dimensional (2D) and three-dimensional (3D) inversion of magnetotelluric data acquired along four semi-parallel profiles crossing the Kalahari craton across the Damara-Ghanzi-Chobe belts (DGC) and extending into the Congo craton. Two dimensional and three-dimensional electrical resistivity models show significant lateral variation in the crust and upper mantle across strike from the younger DGC orogen to the older adjacent cratons. The Damara belt lithosphere is found to be more conductive and significantly thinner than that of the adjacent Congo craton. The Congo craton is characterized by very thick (to depths of 250 km) and resistive (i.e. cold) lithosphere. Resistive upper crustal features are interpreted as caused by igneous intrusions emplaced during Pan-African magmatism. Graphite-bearing calcite marbles and sulfides are widespread in the Damara belt and account for the high crustal conductivity in the Central Zone. The resistivity models provide new constraints on the southern extent of the greater Congo craton, and suggest that the current boundary drawn on geological maps needs revision and that the craton should be extended further south. The storage possibilities for the Karoo Basins were found to be poor because of the very low porosity and permeability of the sandstones, the presence of extensive dolerite sills and dykes. The obvious limitation of the above study is the large spacings between the MT stations (> 10km). This is particularly more limiting in resolving the horizontal layers in the Karoo basin. However the 1D models provide layered Earth models that are consistent with the known geology. The resistivity values from the 1D models allowed porosity of the Ecca and Beaufort group lithologies to be calculated. It is inferred that the porosities values are in the range 5-15 % in the region below the profile. This value is considered too low for CO2 storage as the average porosity of rock used for CO2 is generally more than 10 to 12 percent of the total rock unit volume.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy University of the Witwatersrand School of Geosciences and Dublin Institute for Advanced Studies School of Cosmic Physics Geophysics Section February 2016
Keywords: Magnetotelluric prospecting.; Cratons -- Congo (Democratic Republic); Orogeny.; Plate tectonics.; Damara Mobile Belt (Namibia)